Endothelial Dysfunction and Inflammatory Markers of Vascular Disease - Balta, Sevket (Current Vascular Pharmacology, 2021)
Vascular diseases are the main reason for morbidity and mortality worldwide. As we know, the earlier phase of vascular diseases is endothelial dysfunction in humans, the endothelial tissues play an important role in inflammation, coagulation, and angiogenesis, via organizing ligand-receptor associations and the various mediators' secretion. We can use many inflammatory non-invasive tests (flowmediated dilatation, epicedial fat thickness, carotid-intima media thickness, arterial stiffness and anklebrachial index) for assessing the endothelial function. In addition, many biomarkers (ischemia modified albumin, pentraxin-3, E-selectin, angiopoietin, endothelial cell specific molecule 1, asymmetrical dimethylarginine, von Willebrand factor, endothelial microparticles and endothelial progenitor cells) can be used to evaluate endothelial dysfunction. We have focused on the relationship between endothelial dysfunction and inflammatory markers of vascular disease in this review.
Keywords: Endothelial dysfunction